The Relationship Between Metabolic Presbycusis and Serum Paraoxonase/Arylesterase Activity - Keles, Erol; Kapusuz, Zeliha; Gursu, Mehmet Ferit; Karlidag, Turgut; Kaygusuz, Irfan; Bulmus, Funda Gulcu; Yalcin, Sinasi (Springer India, 2014)
To determine the presence of a relationship between metabolic presbycusis and serum paraoxonase/arylesterase activity. A total of 30 patients who had been admitted to the Ear, Nose, and Throat (ENT) Clinic of Firat University Medical Faculty and diagnosed as metabolic presbycusis were included in the study. The control group was composed of 30 healthy volunteers. Pure tone audiometry and impedencemeter were performed on all subjects included in the study at the audiometry laboratory of the ENT clinic. The presence of a regular hearing curve, a symmetrical sensorineural hearing loss more than 25 dB with preserved speech discrimination were accepted as criteria for metabolic presbycusis. Blood samples were drawn from the patients prior to the hearing tests. The sera were separated for measurements of total cholesterol, triglyceride, high-density lipoprotein, very low-density lipoprotein, low-density lipoprotein, human serum paraoxonase and arylesterase levels, respectively. No statistically significant difference was found between the patient and the control groups in terms of age and gender. Paraoxonase, arylesterase and paraoxonase/arylesterase, high-density lipoprotein levels were found to decrease in the study group and the difference was found to be statistically significant compared to the control group (P < 0.001). Low-density lipoprotein and total cholesterol levels were found to increase in the patient group and the difference was found to be significant compared to the control group (P < 0.001). This study puts forth that especially the type of nutrition and life style are very important with regard to metabolic presbycusis. Furthermore, the results of this study make us think that there could be a relationship between metabolic presbycusis and cardiovascular diseases. In this case, metabolic presbycusis may be a determining parameter in the early diagnosis of cardiovascular diseases. We consider that this study may be the pioneer for further studies conducted with larger patient numbers.
Keywords: Metabolic presbycusis; Paraoxonase; Arylesterase; Lipid